Pandangan dari Tudor City, New York - Abdullah Ahmad, Datuk (Shah Alam, Selangor Darul Ehsan, Malaysia: Times Editions, 2004)
Sociopolitical issues in Malaysia and other countries; collected articles previously published in Utusan Malaysia newspaper from 1996 to 2000.